Predicting vulnerability to management changes in data-limited, small-scale fisheries. (August 2018) - Tilley, Alexander; Herrón, Pilar; Espinosa, Silvana; Angarita, Juliana López; Box, Stephen
Abstract: It is estimated that more than 200 million people worldwide depend on small-scale fisheries for their livelihood, driving the need for fisheries reform to develop effective, local-level governance systems to protect food security and lessen reliance on common resources. However, our ability to impose new management relies on the assessment of vulnerability and adaptive capacity, and the lack of social-ecological data often stifles decision making. Here we test the use of simple fisheries attributes from 33 fishing communities in an understudied, and chronically poor region of the Colombian Pacific, to generate indicators of relative fisheries adaptive capacity, as a proxy for vulnerability to planned management changes. We demonstrate the strengths of this approach using four variables (species assemblage, spatial dependence, gear dependence and compliance), and illustrate how potential threats to livelihoods can be identified early, and with limited data, allowing for management to adapt decision-making accordingly. We show that in the absence of detailed socio-economic information, relatively basic fisheries data recorded by community observers can be applied to decrease uncertainty by providing a rapid characterisation of community vulnerability to management decision-making, in a range of management intervention options. Highlights: Simple fisheries attributes may provide valuable indicators of community vulnerability. Relative vulnerability is modeled for 33 communities in the Colombian Pacific. Model results highlight threats to livelihoods for communities where limited socio-economic data exists. This method allows for prioritization of capacity building needs to strengthen fisheries management.